Effect of Indoor Green Walls on Environment Perception and Well-Being of Occupants in Office Buildings - Aleksandra Lipczynska; Jan Kaczmarczyk; Beata Dziedzic (Energies)
Office employees often face discomfort due to dry air, impacting their productivity. Existing solutions like standalone humidifiers or HVAC-integrated systems are either inefficient or costly. Thus, maintaining optimal air humidity remains a challenge. Green walls offer a potential solution by influencing humidity and air quality. A survey was conducted in five Warsaw office buildings involving 85 participants to investigate this issue. Measurements were taken in three stages: without humidifiers, with standalone humidifiers, and with green walls. The results showed a high acceptance of humidification systems, with green walls being perceived as the most effective in neutralizing air humidity perception. The air quality was rated highest with both humidifiers and green walls. Notably, well-being indicators significantly improved with humidifiers, particularly with the presence of green walls. This study underscores the potential of green walls in improving indoor environmental conditions and occupants’ well-being, offering a promising avenue for enhancing office comfort and efficiency.